Roadmap for precision preclinical x-ray radiation studies. (21st March 2023) - Verhaegen, Frank; Butterworth, Karl T; Chalmers, Anthony J; Coppes, Rob P; de Ruysscher, Dirk; Dobiasch, Sophie; Fenwick, John D; Granton, Patrick V; Heijmans, Stefan H J; Hill, Mark A; Koumenis, Constantinos; Lauber, Kirsten; et al.
Abstract: This Roadmap paper covers the field of precision preclinical x-ray radiation studies in animal models. It is mostly focused on models for cancer and normal tissue response to radiation, but also discusses other disease models. The recent technological evolution in imaging, irradiation, dosimetry and monitoring that have empowered these kinds of studies is discussed, and many developments in the near future are outlined. Finally, clinical translation and reverse translation are discussed.